Quantitative dynamic oxygen 17 MRI at 7.0 T for the cerebral oxygen metabolism in glioma - Paech, Daniel; Nagel, Armin Michael; Schultheiss, Miriam N.; Umathum, Reiner; Regnery, Sebastian; Scherer, Moritz; Wick, Antje; Platt, Tanja; Wick, Wolfgang; Bendszus, Martin; Unterberg, Andreas; Schlemmer, Heinz-Peter; et al. (Radiology, 2020)
BackgroundAltered metabolism is a characteristic of cancer. Because of a shift in glucose metabolism from oxidative phosphorylation to lactate production for energy generation, malignant tumors are characterized by increased glycolysis followed by lactic acid fermentation, even in the presence of abundant oxygen (the Warburg effect).PurposeTo quantitatively investigate dynamic oxygen 17 (17O) MRI in healthy participants and participants with untreated glioma to understand altered cerebral oxygen metabolism in glioma.Materials and MethodsIn this prospective study conducted from September 2016 to June 2018, individuals with newly diagnosed previously untreated glioma (World Health Organization grade II−IV) and healthy volunteers were included. Dynamic 17O MRI was performed with a 7.0-T whole-body system. 17O2 gas inhalation enabled dynamic measurement of the cerebral metabolic rate of oxygen (CMRO2) consumption. In healthy volunteers and participants with glioma, CMRO2 values in gray matter and white matter volumes were compared by using Wilcoxon signed rank tests. In participants with glioma, the tumor volume and tumor subcompartments were compared with normal-appearing gray matter and white matter by using Friedman test followed by Holm-Sidak post hoc tests.ResultsTen participants (mean age, 42 years ± 18 [standard deviation]; nine men) with glioma and three healthy volunteers (mean age, 44 years ± 21; all men) were evaluated. CMRO2 was higher in normal-appearing gray matter compared with white matter in both participants with glioma (2.36 μmol/g/min ± 0.22 vs 0.75 μmol/g/min ± 0.10, respectively) and healthy volunteers (2.38 μmol/g/min ± 0.15 vs 0.63 μmol/g/min ± 0.05, respectively) (P < .001 and P = .03, respectively). In the tumor region, CMRO2 was reduced (high-grade tumor CMRO2, 0.23 μmol/g/min ± 0.07; low-grade tumor CMRO2, 0.39 μmol/g/min ± 0.16; overall CMRO2, 0.34 μmol/g/min ± 0.16) compared with normal-appearing gray matter (P < .001) and normal-appearing white matter (P < .001) in accordance with the Warburg theorem.ConclusionDynamic oxygen 17 MRI method at 7.0 T as a direct metabolic imaging technique in glioma enabled quantitative visualization of the Warburg effect. A general reduction in oxidative glycolysis was observed in accordance with the Warburg theorem.© RSNA, 2020Online supplemental material is available for this article.See also the editorial by Rapalino in this issue.